Explaining the orthography–phonology interface in written corpora: an Optimality–Theoretic approach. Issue 2 (August 2017) - Yildiz, Yasemin
Abstract : This paper has two goals. The first goal is to contribute to the literature of Second Language Writing Systems (L2WS) by focussing on the British University in Dubai (BUiD) and the Arab Learner Corpus (BALC). The second is to demonstrate the close orthography–phonology interface in L2WS and critically address the issue of reform in a script. Unlike previous studies, which provide a holistic and descriptive analysis of all possible spelling errors of Arab learners of English (e.g., Haggan, 1991 ; andRandall and Groom, 2009 ), this study is different in two ways. First, BALC will be interpreted within a markedness framework and a constraint-based theory known as Optimality Theory. Second, particular emphasis will be given to the erroneous spelling forms which appear in lexical items exclusively with complex onset and coda clusters at the phonological level. The motive for this study is to look beyond spelling errors and bridge linguistic theory with learner corpora. The sub-corpora will be identified and categorised by using the Wmatrix3 program (Rayson, 2003, 2005 ). The fulfilment of the above goals will provide new insights for researchers and teachers who are working closely in the areas of L2WS and learner corpora.